Primary hepatoid adenocarcinoma of the lung in patient with silicosis: a case report and literature review - Huang, Lipeng; Chen, Chaoyang; Sun, Qingyu; Yu, Zhichen; Wang, Xiaoyan; Wang, Xinle; Yang, Shuoqi; Jin, Luming; Bu, Liang (Frontiers in Oncology, 2024)
IntroductionHepatoid adenocarcinoma of the lung (HAL) is a special type of adenocarcinoma originating from the lung with adenoid- and hepatocyte-like differentiation. HAL is rare in clinical practice. Here, we present the case of a patient with HAL.Case presentationA 59-year-old man was admitted to the hospital 4 days because of lung mas observed. Chest computed tomography (CT) revealed a lobulated mass shadow in the right lower lobe, approximately 3.5 × 3.3 cm in size. CT-guided percutaneous biopsy of the right lower lung was performed. The pathological results indicated a moderately to poorly differentiated adenocarcinoma. The patient underwent thoracoscopic right middle and lower lobectomy and systematic lymph node dissection. The postoperative pathology was primary HAL, with the staging of T2bN2M0 (stage III A). Recurrence-free survival and overall survival were 6 and 19 months, respectively Preoperatively, the level of alpha-fetoprotein was negative; however, after recurrence, it increased to 87.8.ConclusionPulmonary hepatoid adenocarcinoma is a rare subtype of malignant lung tumor, combined silicosis is more rare. Early surgical intervention can benefit patients in the early stages of the disease, whereas chemotherapy remains the main systemic treatment modality for postoperative and advanced stages. With the increasing popularity of genetic testing, it is important to focus on improving genetic examination.